Library of Congress Classification basics - Suja', Balqis (2010)
This is a two-hour programme for support staff group to enable them understand the basic structure of LCC, as well as subdivision techniques used throughout LCC, and how to read LCC call number. The lecture started with concepts on subject analysis and classification and ended with individual exercise on how to organize items with LCC call number on the shelf.